Probiotics and prebiotics - characteristics and application among children and adolescents - Fabian-Danielewska, Anna; Malita, Agnieszka (Journal of Education, Health and Sport, 2018)
Dietary supplements containing live microorganisms and nutrients that support the human body are used with ever increasing frequency by parents among children and adolescents. Preparations available on the market have a diverse composition, which may be problematic when deciding which product to choose and in which disease entity to use it. The purpose of the articles is to approximate the characteristics of probiotics and prebiotics and determine the indications for their use.